Comparative Study: Quality of Life of Elderly with Presbycusis Who Live at Home with TresnaWreda Nursing Homes - Zachreini, Indra; N, Purnami; D, Soetjipto; J, Bashiruddin (International Journal of Psychosocial Rehabilitation, 2020)
Age-related hearing loss, or presbycusis, is one of the most common conditions affecting the elderly globally. In elderly patients, the consequences due to hearing loss are very substantial which potentially disturb social interaction and communication thus influences their quality of life, one of which is social interactions and communication. This research is an observational analytic study to compare the quality of life of the elderly with presbycusis who lived at home and those living at TresnaWreda nursing homes based on Hearing Handicap for Elderly Screening (HHIE-S) questionnaire using cross sectional study. Research results noted, differences in quality of life between elderly with presbycusis who live at home with TresnaWreda nursing homes which p-value 0.020. There was differences of quality of life between elderly with presbycusis who live at home with those living at TresnaWreda nursing homes.